Pengaruh Modal Usaha, Kemampuan Manajerial dan Kualitas Sumber Daya Manusia Terhadap Pemberdayaan UMKM di Kecamatan Tombatu Kabupaten Minahasa Tenggara - Kezia Keren Pandey; Michael Mamentu; Stefanus Sampe (Universitas Sam Ratulangi, 2022)
This study aims to determine the effect of venture capital, managerial ability and quality of human resources on the empowerment of UMKMs in Tombatu District, Southeast Minahasa Regency. This study used a sample of 50 respondents with the status of business actors in Tombatu District, Southeast Minahasa Regency. Quantitative analysis technique with multiple linear analysis is used in this research. The statistical tests carried out in this study were validity tests, reliability tests, normality tests, tests, multicollinearity tests, determination tests, partial tests and simultaneous tests. Through validity and reliability tests, it was found that the questionnaires in this study were valid and reliable. Through the determination test, it was found that business capital, managerial ability, and quality of human resources had an effect of 52.6% on the empowerment of micro, small and medium enterprises and the rest was influenced by other variables not examined in this study. Overall, business capital, managerial ability and the quality of human resources together have a positive and significant impact on the empowerment of Micro, Small and Medium Enterprises (UMKM). owned by Micro, Small and Medium Enterprises (UMKM).